Emerging trends and research priorities in premature ovarian insufficiency genes: a bibliometric and visualization study - Xi Zhao; Wenying Shi; Xiaojuan Liu; Wei Zhang (Taylor & Francis Group, 2023)
Purpose To illustrate the results achieved by genes in premature ovarian insufficiency (POI) and collaborations in the field, and to explore key themes and future directions.Methods Articles and reviews related to POI genes published between 1990 and 2022 were retrieved from the Web of Science core collection (WoSCC) for the total bibliometric analysis. Tools were analyzed for publication, country, institution, journal, authors, reference, keywords, subject categories, funding agencies, and research hotspots using a bibliometric online analysis platform, Bibliographic Co-occurrence Matrix Builder (BICOMB), CiteSpace V, and VOSviewer.Results A total of 2,232 papers were included in this study. Articles were published in 52 countries, with the United States publishing the most, followed by China. A total of 308 institutions contributed to relevant publications. Shandong University published the most papers. Qin Y's team published the most relevant papers. Human reproduction and fertility and sterility are the two journals with the most papers. X-chromosome abnormalities, transcription factor mutations, and FMR1 genes are the directions of more POI, and DNA repair is the keyword of the research frontier in recent years.Conclusions This study summarizes the relevant literature on POI gene research for the first time and analyzes the current hotspots and future trends in this field. The findings can further reveal the etiology, diagnosis, and treatment of POI, which is beneficial for researchers to grasp the genetic dynamics of POI women.